Dental autotransplantation – rehabilitation and social inclusion: na integrative review (Research, Society and Development, 2023)
Dental autotransplantation is a surgical technique in which a tooth is removed from its original place and starts to occupy another space in one of the arches of the same patient. Generally, these new spaces are aesthetic areas, such as the extension of the smile line, or in areas of greater functionality. Trauma that results in tooth loss, agenesis, extensive and irreversible destruction by caries, may require high-cost, time-consuming and often inefficient rehabilitation processes, circumstances that end up imposing on the individual a forced acceptance of their condition: compromised aesthetics, subfunction mastication and phonation, and thus, cause low self-esteem. In this sense, this article aimed to carry out an integrative review on autotransplantation, highlighting the advantages and challenges in the face of the numerous evolutions of the technique in the private sphere to the detriment of the restrictions and limited possibilities of the public service. However, the research demonstrated its viability, which could be offered by specialized care/SUS. The textual results of the literature published in the last 10 years were presented, and for the construction of this review, the following databases were used: PubMED, Scientific Electronic Library Online (SciELO) and Google Scholar, with articles in English and Portuguese. Thirty-two articles were analyzed, which revealed the possible applicability of the surgical technique by the public service, which will allow an improvement in the quality of life of individuals undergoing surgery, guaranteeing comprehensive care and inclusion in social representativeness cycles.